Optimasi Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Terbaik Menggunakan Simple Additive Weighting Pada PT. Asuransi Ciputra Indonesia - Wahyu Saputro; Kristianto Kristianto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
PT Asuransi Ciputra Indonesia or known as Ciputralife is a subsidiary of PT. Asuransi Ciputra Indonesia. Ciputra International and PT. Tunas Andalan Pratama, which was formed with a vision to build a better future. This company is inseparable from competition in the growing and competitive business world. This spurs the company to improve its quality, so Ciputralife needs to assess the performance of its employees. Performance appraisal is to determine the level of success in carrying out tasks. The goal is to produce a better and easier assessment of employee abilities to determine the appropriate work position. The partner's problem can be solved by the Simple Additive Weighting (SAW) method where the system will determine the results based on the input provided by the user. This technical application is offered to partners as a form of dissemination of knowledge. The methods used in dissemination activities include data collection by documentation, observation, and interviews with partners, then continued with analysis to find out the assessment criteria. The results of the analysis are submitted to partners for consideration.